A new method for matching gold nanoparticle‐based time–temperature indicators with muffins without obtaining activation energy. Issue 8 (20th July 2020) - Zhang, Lixuan; Sun, Ruonan; Yu, Hufei; Yu, Hailong; Xu, Gaolei; Deng, Liming; Qian, Jing
Abstract : Abstract: Time–temperature indicators (TTIs) can monitor the quality and safety of food. A new temperature–time point comparison method was proposed to match TTIs with food. This method omits the step of calculating activation energy ( E a ). It only compares the difference between TTI response time and food shelf life to determine their matching degree. Taking gold nanoparticle‐based TTIs and muffins as experimental objects, the new and the traditional matching methods were used to match the absorbance of TTI and the peroxide value of muffins. The two results are not significantly different. TTIs with gelatin solution and gold precursor solution concentration of 150.00 and 2.05 mg/mL, respectively, can show the quality of muffins. TTIs changed from light yellow to pink and finally appeared deep purple. The deep purple represented spoilage and inedibility of muffins. Comparing E a of food and that of TTIs can preliminarily evaluate their matching degree, improving the experiment efficiency. Hence, it is reasonable to use the traditional matching method in most cases, and use the new method only when E a of food cannot be obtained. Practical Application: The deterioration rate of food is usually calculated by developing kinetic models of characteristic quality parameters. When the reaction rate is unavailable or inaccurate, the activation energy of food cannot be obtained. In this case, it is impossible to match TTIs with food based on the traditional method. This research develops a new matching method and helps TTIs and food to be matched without considering activation energy. It will promote the application of TTIs in more products.